2013 Spillover Report. (Policy Papers; Policy Paper ;, 2013)
Five years after the global financial crisis, the severe tensions and risks rooted last year in some of the 'Systemic five' (S5)-China, euro area, Japan, United Kingdom, United States--have abated but all five are still operating below potential, id est, they are not contributing to global activity as much as they might: if they could somehow close their output gaps, global output would be closer to potential by 3 percentage points. Meanwhile, many parts of the rest of the world have been at or near potential. Most recently though, there have been signs of accelerated recovery in the United States and slowdown in emerging markets. This continued divergence in cyclical positions poses a global challenge, namely to find policies that help the S5 close their output gap without over-stimulating or over-tightening, through spillovers, economies that do not need it.